Effectiveness Of Date Dry Seed as a Natural Coagulant in Wastewater Treatment Process - Abdul Rahman Adrin, Muhammad Hakim; Ngadiman, Norhayati; Abdullah, Noorul Hudai; Hamdan, Rafidah; Siddiqui, Zuhaib (International Journal of Sustainable Construction Engineering and Technology, 2024)
Organic and inorganic compounds, heavy metals, and insoluble substances contaminate industrial effluents. The environmental hurdles for the textile industry stem from the diversity in colours and chemical elements present in its waste output. The coagulation-flocculation method is highly regarded for its capability to remove biodegradable substances, suspended solids, turbidity, and colouration from industrial wastewater. However, the application of chemical coagulants, despite their effectiveness, poses significant drawbacks due to their high cost and the generation of sizable quantities of non-biodegradable waste and metallic traces in the water, potentially leading to contamination and health hazards. An alternative approach gaining attention involves the use of plant-based, natural coagulants. These are not only non-toxic and biodegradable but also environmentally sustainable. This study aims to evaluate the potential of date seed extract as a natural coagulant in treating wastewater from the textile industry. The extraction of the coagulant was performed using distilled water and NaCl. Parameters such as Chemical Oxygen Demand (COD), turbidity, ammonia nitrogen, and pH levels were measured to assess the purification efficacy of the date seed on the textile wastewater. Experiment results revealed that the date seeds have remarkable coagulation properties. The optimal dosage of date seed to remove COD, ammonium nitrogen, and turbidity was determined to be 56.19%, 43.33%, and 83.96%, respectively. The concentration of 2.0M NaCl is optimal for removing COD and ammonia nitrogen, whereas the concentration of 1.0M NaCl is optimal for eliminating turbidity. The research findings demonstrated the potential benefits of using date seed as a natural coagulant in treating textile industrial effluent.